(untitled) (Indian Journal of Animal Production and Management, 2025)
Avian influenza (AI), commonly known as bird flu, is a highly contagious viral infection that affects a wide range of bird species, including domestic poultry. Among the various subtypes of avian influenza viruses, H9N2 is one of the most widespread and economically significant low pathogenic avian influenza viruses (LPAIV) in poultry. First identified in the 1960s, H9N2 has since become endemic in many regions, particularly in Asia, the Middle East, and North Africa (Peacock et al., 2019). Although it is classified as low pathogenic, meaning it typically causes mild clinical signs, H9N2 can still lead to substantial economic losses in the poultry industry due to reduced egg production, poor growth rates, and increased susceptibility to secondary infections (Butt et al., 2002).